EEG AND EVENT-RELATED POTENTIAL (P300) IN ELDERLY PATIENTS WITH APHASIA AND EPILEPSY AFTER STROKE - V. V. Gnezditskiy; O. S. Korepina; V. A. Karlov; E. E. Koshyrnikova; A. V. Chatskaya (Эпилепсия и пароксизмальные состояния, 2016)
Objective. We assessed the changes in EEG and event-related potential (P300) in elderly patients with poststroke aphasia and epilepsy.Materials and Methods. We examined 57 patients with poststroke aphasia (age 55-79 years). Cortical aphasia was revealed in 47 cases, and 10 patients had subcortical aphasia. Control group consisted patients with chronic brain chronic brain ischemia and healthy persons.Results. Local slow activity in the left hemisphere in EEG were revealed in 78% of patients with cortical aphasia, and in 20% of cases with subcortical aphasia. Local epileptic activity along with slow activity was spike-and-slow-wave complexes and sharp waves; temporal intermittent delta activity (TIRDA); both spike-and-wave complexes and TIRDA. In two cases epileptic activity was revealed as periodic lateralizing epileptiform discharges (PLEDs) besides local slow waves, and may deteriorate the aphasia. According to P300 data patients with poststroke aphasia hadn’t severe cognitive impairment, and the worst changes were noted in the group with chronic brain ischemia. In some patients with heavy aphasia it was possible to recorded P300 in passive perception of stimuli. Conclusion. In cases with PLEDs and persistent epileptic activity antiepileptic treatment probably reduces the aphasia. P300 is important in diagnostic of cognitive decline in patients with poststroke aphasia, especially when aphasia is heavy and neuropsychological tests can’t be done.